Погребения со зливкинскими традициями на могильнике у посёлка Новодачное на реке Лугань - Красильников, К.И.; Красильникова, Л.И. (Степи Европы в эпоху средневековья, 2012)
Эпиграфом к материалам, полученным в результате раскопок части могильника у пос.Но- водачное, проведённых экспедицией Луганского пединститута в 1992 г (Красильников К.И., Тельнова Л.И., 1992), могут служить строки, написанные С.А.Плетнёвой: “Более скромным, но тоже с ранее не встречавшимися особенностями является могильник у пос.Новодачное, начатый раскапываться в 1992 году...". The paper presents the finds of excavations of 1992 and 2001 at a burial ground of the Saltov- Maiaki culture. The explored area was 1210 square meters where 24 burials were discovered, with 13 of them undamaged and 11 fully or partially exhumed. The constructions of burial graves, blocks, inhumation poses, grave goods (i.e. jewelry, plates and dishes, altars), orientation of the deceased and other features generally correspond to the burial system known as “Zlivki type” burials of the Proto- Bulgarians of the 9th century. The issues of funeral rites, orientation, ethnicity and social status of the deceased have been dicussed.